Divergent evolution and niche differentiation within the common peatmoss Sphagnum magellanicum. Issue 7 (28th July 2017) - Yousefi, Narjes; Hassel, Kristian; Flatberg, Kjell Ivar; Kemppainen, Petri; Trucchi, Emiliano; Shaw, A. Jonathan; Kyrkjeeide, Magni Olsen; Szövényi, Péter; Stenøien, Hans K.
Abstract : PREMISE OF THE STUDY: Populations with phenotypic polymorphism in discrete characters may be good models for investigating genome evolution and speciation. Sphagnum magellanicum Brid. is found throughout the northern hemisphere, and despite considerable variation in morphological characters, it is considered one of the least taxonomically controversial peatmoss species. We have observed two main morphs of the species associated with different microhabitats. Here we investigated the genomic and environmental basis of this intraspecific morphological variation. METHODS: We conducted transplant and common garden experiments to test whether the two morphs are genetically differentiated. We then used RAD‐sequencing to quantify the genomic divergence between the morphs and approximate Bayesian computation (ABC) to infer the most likely demographic scenario explaining the genome‐wide differentiation of the two morphs. KEY RESULTS: We found that genomic differentiation between the two morphs is unexpectedly high and that several of the differentiated morphological characters have a genetic basis. Using simulation approaches, we found support for a scenario of ancient divergence followed by recent secondary contact. CONCLUSIONS: We show that the two morphs represent the two main genetic clusters previously found worldwide. Our results demonstrate that relatively minor morphological differentiation in a presumed phenotypically plastic peatmoss may be associated with massive divergence across the genome.